Seismic performance and effective isolation of a large multilayered underground subway station. Issue 142 (March 2021) - Jing, Yang; Haiyang, Zhuang; Wei, Wang; Zhenghua, Zhou; Guoxing, Chen
Abstract: In this paper, the seismic performance of a reinforced concrete (RC)-framed underground subway station structure which has three stories and three spans was analyzed firstly under strong earthquakes. It was found that the central columns in the top and the bottom stories were the weakest seismic components in this type of underground structure. Thus, lead-core rubber bearings (LRBs) were installed at the central column-tops of the structure, and the seismic performance of the underground station structure with LRBs was also studied. The results show that LRBs can reduce the seismic damage to the central columns and interior slabs and the lateral deformation of the central columns effectively. While the installation of LRBs will also change the internal force transfer characteristics and energy distribution of the large underground structure and increase the seismic damage to the top and bottom slabs and side walls to some extent. In particular, when LRBs were only set on the central column-tops in the top and bottom stories, which have the most unfavorable seismic performance in the underground structure, the seismic damage to the central columns without LRBs was significantly exacerbated. The isolation method of installing LRBs at the top of the central columns in each story was clearly superior and could ensure that the underground station structure would not collapse due to serious damage of the columns under strong earthquakes. Highlights: Seismic performances of a special underground structure were investigated. New criterions to evaluate its seismic performance and damage were suggested. Based on its seismic performance, two types isolation methods were designed. Influence of LRB on the seismic performance of isolated structure were analyzed. Suggests were made for the isolation design of this large underground structure.